Candida Extracellular Nucleotide Metabolism Promotes Neutrophils Extracellular Traps Escape - Afonso, Mariana; Mestre, Ana Rita; Silva, Guilherme; Almeida, Ana Catarina; Cunha, Rodrigo A.; Meyer-Fernandes, José Roberto; Gonçalves, Teresa; Rodrigues, Lisa (Frontiers in Cellular and Infection Microbiology, 2021)
Host innate immunity is fundamental to the resistance against Candida albicans and Candida glabrata infection, two of the most important agents contributing to human fungal infections. Phagocytic cells such as neutrophils, constitute the first line of host defense mechanisms, and the release of neutrophil extracellular traps (NETs) represent an important strategy to immobilize and to kill invading microorganisms, arresting the establishment of infection. The purinergic system operates an important role in the homeostasis of immunity and inflammation, and ectophosphatase and ectonucleotidase activities are recognized as essential for survival strategies and infectious potential of several pathogens. The expression and unique activity of a 3’-nucleotidase/nuclease (3’NT/NU), able to hydrolyze not only AMP but also nucleic acids, has been considered as part of a possible mechanism of microbes to escape from NETs. The aim of the present study was to evaluate if yeasts escape from the NET-mediated killing, through their 3’NT/NU enzymatic activity contributing to NET-hydrolysis. After demonstrating the presence of 3’NT/NU activity in C. albicans, C. glabrata and Saccharomyces cerevisiae, we show that, during neutrophils-Candida interaction, when NETs formation and release are triggered, NETs digestion occurs and this process of NETs disruption promoted by yeast cells was prevented by ammonium tetrathiomolybdate (TTM), a 3’NT/NU inhibitor. In conclusion, although the exact nature and specificity of yeasts ectonucleotidases are not completely unraveled, we highlight the importance of these enzymes in the context of infection, helping yeasts to overcome host defenses, whereby C. albicans and C. glabrata can escape NET-mediate killing through their 3’NT/NU activity.